Ozone (O3): an excellent adjunctive tool in medical and surgical management of patient - Thakkar, Vipin; Thakkar, Harsh (International Journal of Research in Medical Sciences, 2017)
In the condition like increasing susceptibility to allergic reaction & weaken response to antibiotics, along with constantly growing prices for medical treatment, new non-medicinal methods are to be appreciated. The history of medical ozone starts in the XX century. The pioneers to apply ozone in clinical practice were E. Payer, A. Fish and H. Wolf. Ozone as an antiseptic means had been known and used from the beginning of the XX century, however, extensive and systemic research in the field of ozone therapy started in Germany in mid 70s, when ozone-resistant polymer materials and convenient ozone generating equipment came into every day clinical practice. Ozone (O3) therapy due to its disinfection effect & its capacity to transport & release oxygen into tissues is gaining a justified recognizing in many countries of the world. O3 therapy can produce its immune modulators, anti-inflammatory, bactericidal, virucidal, fungicidal, analgesics & other effects. Considering this the purpose of this literature is to highlight the significance of Ozone as an excellent adjunctive tool in the management of various medical and surgical conditions.